Delineation of Mitochondrial DNA Variants From Exome Sequencing Data and Association of Haplogroups With Obesity in Kuwait - Dashti, Mohammed; Alsaleh, Hussain; Eaaswarkhanth, Muthukrishnan; John, Sumi Elsa; Nizam, Rasheeba; Melhem, Motasem; Hebbar, Prashantha; Sharma, Prem; Al-Mulla, Fahd; Thanaraj, Thangavel Alphonse (Frontiers in Genetics, 2021)
BACKGROUND/OBJECTIVES Whole exome sequencing is a valuable tool to determine genetic variations that are associated with rare and common health conditions. Limited number of studies demonstrated that mitochondrial DNA can be captured using whole exome sequencing. Previous studies have suggested that mitochondrial DNA variants and haplogroup lineages are associated with obesity. Therefore, we investigated the role of mitochondrial variants and haplogroups contributing to the risk of obesity in Arabs in Kuwait using exome sequencing data. SUBJECTS/METHODS Indirect mitochondrial genomes were extracted from exome sequencing data from 288 unrelated native Arab individuals from Kuwait. The cohort was divided into obese [body mass index (BMI) ≥30 kg/m2] and non-obese (BMI <30 kg/m2) groups. Mitochondrial variants were identified, and haplogroups were classified and compared to other sequencing technologies. Statistical analysis was performed to determine associations and identify mitochondrial variants and haplogroups affecting obesity. RESULTS Haplogroup R showed a protective effect on obesity [odds ratio (OR) = 0.311; P =0.006], whereas haplogroup L individuals were at high risk of obesity (OR = 2.285; P = 0.046). Significant differences in mitochondrial variants between the obese and nonobese groups, which were mainly haplogroup-defining mutations and were involved in processes in energy generation. The majority of mitochondrial variants and haplogroups extracted from exome were in agreement with technical replica from Sanger and whole genome sequencing. CONCLUSIONS This is the first to utilize whole-exome data to extract entire mitochondrial haplogroups to study association with obesity in an Arab population.